The Significance of Planetary Alignments: Astronomical, Cultural, and Theological Insights - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2025)
Planetary alignments have intrigued astronomers, cultural historians, and religious scholars for centuries as a point of intersection between science and human belief systems. These celestial events have historically been associated with harmony, transformation, and symbolism, with varying interpretations across civilizations. This study modeled planetary alignments involving the Sun, Mercury, Venus, Earth, and Mars from 2000 to 2100. The analysis employed elliptical orbital mechanics to predict the timing and frequency of these events, focusing on angular separations and gravitational interplay among the celestial bodies. The findings showed more frequent alignments between Earth and Mars in 2025, 2051, 2076, and 2100. However, a simultaneous alignment involving all five planets—Sun, Mercury, Venus, Earth, and Mars—was rare, occurring only once in 2025. This singular event highlights the intricate dynamics of orbital mechanics and gravitational forces that govern planetary motion. The alignments were discovered to have significant cultural and spiritual, representing themes of peace and rebirth in many different traditions. The study underscores the importance of interdisciplinary collaboration to explore the multifaceted significance of celestial events, bridging the realms of astronomy, cultural studies, and spirituality. The rare 2025 alignment offers a unique opportunity for public engagement in astronomy, fostering a deeper appreciation of the cosmos. Moreover, preserving and integrating cultural interpretations of planetary alignments can promote a holistic understanding of their significance.